2017
DOI: 10.4049/jimmunol.1700443
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of IRAK1 Ubiquitination Determines Glucocorticoid Sensitivity for TLR9-Induced Inflammation in Macrophages

Abstract: Inflammatory responses are controlled by signaling mediators that are regulated by various posttranslational modifications. Recently, transcription-independent functions for glucocorticoids (GC) in restraining inflammation have emerged, but the underlying mechanisms are unknown. In this study, we report that GC receptor (GR)–mediated actions of GC acutely suppress TLR9-induced inflammation via inhibition of IL-1R–associated kinase 1 (IRAK1) ubiquitination. β-TrCP–IRAK1 interaction is required for K48-linked ub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 46 publications
(73 reference statements)
3
16
0
Order By: Relevance
“…Activation of this signaling pathway further regulates IRAK1 mediated activation of TNF Receptor Associated Factor 6 (TRAF6) and Transforming growth factor beta-activated kinase 1 (TAK1) that further causes activation of TGF-Beta Activated Kinase 1 (TAB1). Thus our findings are well correlated with earlier reports for different convergent signaling pathways (Kong et al, 2017; Dong et al, 2006; Cui et al, 2012; Xiong et al, 2011, Johnsen and Whitehead 2006; Rhyasen and Starczynowski 2014, O’Neill and Bowie 2007, Conforti et al, 2010; Salaun et al, 2006; Gambara et al, 2014; Oshiumi et al, 2003; Yamamoto 2003, Ma et al, 2018, Klein and Assoian 2008, Alt et al, 2000).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Activation of this signaling pathway further regulates IRAK1 mediated activation of TNF Receptor Associated Factor 6 (TRAF6) and Transforming growth factor beta-activated kinase 1 (TAK1) that further causes activation of TGF-Beta Activated Kinase 1 (TAB1). Thus our findings are well correlated with earlier reports for different convergent signaling pathways (Kong et al, 2017; Dong et al, 2006; Cui et al, 2012; Xiong et al, 2011, Johnsen and Whitehead 2006; Rhyasen and Starczynowski 2014, O’Neill and Bowie 2007, Conforti et al, 2010; Salaun et al, 2006; Gambara et al, 2014; Oshiumi et al, 2003; Yamamoto 2003, Ma et al, 2018, Klein and Assoian 2008, Alt et al, 2000).…”
Section: Discussionsupporting
confidence: 93%
“…But this proliferative effect has been perturbed by the addition of MyD88 inhibitor suggesting that the said effect of TLR 3 is mediated by the MyD88. In the present investigation, TLR3 activation through TLR3 ligand stimulated the expression of downstream signaling factors, including IRAK1, TRAF6, TAB1, and TAK1 and suppressed the MyD88 inhibitor that correlates with other signaling cascade (Kong et al, 2017). It has been reported that activation of other TLRs, in contrast to TLR3, can induce canonical pathway through MyD88 mediated activation of Interleukin 1 Receptor Associated Kinase 1(IRAK1).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…To describe this pattern, model F assumed an inhibition of mRNA production by DR n in conjunction with a secondary, DR-mediated process inhibiting the rate of target protein degradation. The basis of this putative nongenomic, post-translational model of CS action is a recently identified molecular mechanism mediated by dexamethasone (Kong et al, 2017). The mRNA and protein expressions of 10 mRNA and their corresponding proteins were well described by this model.…”
Section: Pharmacogenomics and Proteomicsmentioning
confidence: 89%
“…Our understanding of the biology and mechanisms behind this observation is limited. However, recent studies in macrophages by Kong et al (2017) have provided key insights into a novel posttranslational mechanism of glucocorticoid signaling. They demonstrated that dexamethasone-activated GR acts in a rapid, transcription-independent manner to interact with an inflammation-related cytoplasmic protein IRAK1 and thus interferes with protein-protein interactions between IRAK1 and b-TrCP (an E3 ligase), and subsequently suppresses K48 linkage-specific ubiquitination of IRAK1.…”
Section: Discussionmentioning
confidence: 99%